Bill Heusinkveld and Marjorie Heusinkveld letter to Thomas H. Kent regarding field notes, December 3, 1981 - Heusinkveld, Marjorieet al; Heusinkveld, Billet al (1981)
Field notes were contributed by Bill Heusinkveld and Marjorie Heusinkveld in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed